Answer:
480
Step-by-step explanation:
Answer:
9* 3 ^ (x-2)
Step-by-step explanation:
g(x) = 3^x
We know a^ (b) * a^(c) = a^ (b+c)
9* 3 ^ (x+2) = 3^2 * 3 ^(x+2) = 3^(2+x+2) = 3^x+4 not equal to 3^x
3*(9^(x+2)) = 3*3^2(x+2) = 3^1 * 3^(2x+4) =3^(2x+4+1) = 3^(2x+5) not equal
9* 3 ^ (x-2) = 3^2 * 3 ^(x-2) = 3^(2+x-2) = 3^x equal to 3^x
3*(9^(x-2)) = 3*3^2(x-2) = 3^1 * 3^(2x-4) =3^(2x-4+1) = 3^(2x-3) not equal
Answer:
B
Step-by-step explanation:
Answer:
C) 78
Step-by-step explanation:
its technically 77.5714... but rounds to 78, hope that helps
Answer:
4/7
Step-by-step explanation:
5/7 x (1/5+3/5) = 5/7 x 4/5 = 4/7